Sodium-ion battery with high stability and long service life and preparation method thereof
The sol-gel method is used to prepare sodium transition metal phosphate composite materials and surface nanohardened carbon materials as positive and negative electrode active materials. Combined with a simple assembly process, the problem of insufficient cycle stability and life of sodium ion batteries is solved, and the battery performance with high stability and long life is achieved, which is suitable for large-scale production.
Patent Information
- Application Number
- CN202510537336.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-27
- Publication Date
- 2025-07-08
AI Technical Summary
Existing sodium ion batteries have shortcomings in cycle stability and life, especially in low temperature environments, and their performance is significantly reduced, and their preparation process is complicated, making them not suitable for large-scale production.
The positive electrode active substances sodium transition metal phosphate composite material and surface nanohardened carbon material are prepared as negative electrode active substances by sol-gel method, and the battery is prepared through a simple assembly process, using polyanionic separators and specific electrolytes to improve the electrochemical stability and cycle life of the battery.
The cycle life and capacity retention rate of sodium ion batteries have been significantly improved, and the battery life is extended by more than 50%, and the capacity retention rate still reaches more than 85% after 1,000 cycles, making it suitable for large-scale industrial production.
Smart Images

Figure CN120280534A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of sodium-ion batteries, and particularly to a sodium-ion battery with high stability and long life and a preparation method thereof. Background Art
[0002] In the context of today's energy transformation, the importance of energy storage technology has become increasingly prominent. Sodium-ion batteries have become one of the most promising energy storage solutions due to the abundant sodium resources and low cost.
[0003] However, current sodium-ion batteries still face many challenges in practical applications. For example, the cycle stability of the battery is poor, and after multiple charge and discharge cycles, the capacity is prone to rapid decay, which greatly reduces the service life of the battery and increases the use cost. At the same time, under different working environmental temperatures, the battery performance fluctuates greatly, making it difficult to meet the requirements of various complex working conditions. For example, in a low-temperature environment, the charge and discharge efficiency of the battery is significantly reduced and it cannot work properly.
[0004] In addition, existing preparation processes are often relatively complex, which is not conducive to large-scale and low-cost production. Therefore, developing a sodium-ion battery with high stability, long life and a simple preparation process is of great significance for promoting the wide application of sodium-ion batteries. Summary of the Invention
[0005] The purpose of the present invention is to provide a sodium-ion battery with high stability and long life and a preparation method thereof, and solve the following technical problems:
[0006] How to improve the electrochemical stability of sodium-ion batteries.
[0007] The purpose of the present invention can be achieved by the following technical solutions:
[0008] In the first aspect, the present invention discloses a sodium-ion battery with high stability and long life, including a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator. The positive electrode sheet includes a positive electrode current collector and a positive electrode active material coated on the positive electrode current collector. The negative electrode sheet includes a negative electrode current collector and a negative electrode active material coated on the negative electrode current collector; the positive electrode active material is a sodium transition metal phosphate composite material; the negative electrode active material is a surface-nanostructured hard carbon material.
[0009] Further, the preparation method of the sodium transition metal phosphate composite material is as follows: a transition metal salt, a phosphoric acid source, a sodium source and a dopant are mixed according to a molar ratio of metal ions:P:Na:doping ions = 1.05:1:1.03:0.1, and a precursor is prepared by a sol-gel method, and then calcined at 750-800 °C for 10-12 h in a mixed gas atmosphere of nitrogen and hydrogen with a volume ratio of 9:1 to obtain the sodium transition metal phosphate composite material.
[0010] Furthermore, the preparation method of the precursor by the sol-gel method is as follows:
[0011] Dissolve the transition metal salt in deionized water. After mixing the transition metal salt, phosphate source, sodium source, and dopant in proportion, dissolve them in deionized water. Heat in a water bath at 60 - 80 °C and continuously stir until the solution becomes a transparent sol (about 2 - 4 hours). Then stand for 24 hours to form a gel. Subsequently, quickly freeze the gel with liquid nitrogen and then freeze-dry it (-50 °C, vacuum degree ≤ 10 Pa, 24 hours), and keep it at 300 °C for 2 hours.
[0012] Furthermore, the transition metal salt is manganese sulfate (MnSO4), cobalt nitrate (Co(NO3)2), nickel nitrate (Ni(NO3)2), iron nitrate (Fe(NO3)3), manganese acetate (Mn(CH3COO)2), cobalt oxalate (CoC2O4), iron chloride (FeCl3), and / or; the phosphate source is ammonium dihydrogen phosphate (NH4H2PO4), diammonium hydrogen phosphate ((NH4)2HPO4), sodium phosphate (Na3PO4), sodium pyrophosphate (Na4P2O7), phosphoric acid (H3PO4), and / or; the sodium source is sodium bicarbonate (NaHCO3), sodium acetate (Na3C6H5O7), sodium oxalate (Na2C2O4), sodium citrate (Na3C6H5O7), sodium nitrate (NaNO3), and / or; the dopant is Mg 2+ 、Al 3+ 、Ti 4+ 、Zr 4+ 、F - ,and / or.
[0013] Furthermore, the preparation method of the positive electrode plate is as follows: Mix the sodium transition metal phosphate composite material, conductive agent, and binder in a weight ratio of (80 - 82):(15 - 13):5, then add them to N-methylpyrrolidone (NMP) solvent, stir evenly to form a positive electrode slurry with a solute mass fraction of 65%, then coat the positive electrode slurry on the positive electrode current collector, the coating thickness is 145 - 155 um, then dry at 120 °C for 12 h, and finally roll-press to obtain a positive electrode plate with a density of 3.2 g / cm 3 of the positive electrode plate.
[0014] Furthermore, the preparation method of the surface-nanostructured hard carbon material is as follows: Ball-mill the hard carbon with zirconia grinding balls at a ball-to-material ratio of 20:1 at 500 rpm for 20 h to obtain the surface-nanostructured hard carbon material.
[0015] Furthermore, the specific surface area of the surface-nanostructured hard carbon material is ≥ 200 m 2 / g, and the D50 is 50 - 100 nm.
[0016] Further, the preparation method of the negative electrode plate is as follows: Mix the surface-nanostructured hard carbon material, conductive agent, and binder in a weight ratio of (83 - 85):(10 - 12):5, then add pure water and stir evenly to form a negative electrode slurry with a solute mass fraction of 65%. Then coat the negative electrode slurry on the negative current collector with a coating thickness of 115 - 125 um, dry it at 80 °C for 8 h, and finally roll press to obtain a negative electrode plate with a density of 1.8 g / cm 3 of the negative electrode plate.
[0017] Further, the preparation method of the electrolyte is as follows: Dissolve the conductive sodium salt in an organic solvent to form a mixed solution with a concentration of 1.2 mol / L; then add a functional additive to the mixed solution and stir and mix well under argon protection to obtain the electrolyte.
[0018] Further, the conductive sodium salt is a sodium bis(fluorosulfonyl)imide derivative; the organic solvent is a mixed solvent composed of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:2; the functional additive includes a film-forming additive and an antioxidant additive. Among them, the film-forming additive is vinylene carbonate, and the antioxidant additive is 2,7-di-tert-butylphenothiazine;
[0019] Preferably, the mass fraction of vinylene carbonate is 1%, and the mass fraction of 2,7-di-tert-butylphenothiazine is 0.5%.
[0020] In a second aspect, the present invention also discloses a preparation method of a high-stability and long-life sodium-ion battery as described above, which is characterized by including the following steps: Assemble the positive electrode plate, separator, and negative electrode plate into an electric core in sequence, put it into a battery case, inject the electrolyte, and finally obtain the high-stability and long-life sodium-ion battery through encapsulation and formation process treatment.
[0021] Preferably, the material of the separator is a polyanion-type compound (NFPP) or polyolefin.
[0022] The beneficial effects of the present invention:
[0023] 1. In the sodium-ion battery of the present invention, the positive active material in the positive electrode sheet is a sodium transition metal phosphate composite material, which is prepared by mixing transition metal salts, a phosphate source, a sodium source, and a dopant in proportion, using the sol-gel method to prepare a precursor, and then calcining it in an atmosphere of a mixed gas of nitrogen and hydrogen; the negative active material in the negative electrode sheet is a surface-nanostructured hard carbon material, and its surface is processed by precision nanostructuring to achieve a higher specific surface area and a more uniform particle size; when the battery is working, the positive active material and the negative active material play a synergistic role, which can significantly improve the cycle stability and service life of the battery; under the same test conditions, compared with the prior art, the cycle life of the sodium-ion battery of the present invention is increased by more than 50%, and the capacity retention rate can still reach more than 85% after 1000 cycles, with excellent electrochemical stability and a longer service life.
[0024] 2. In the sodium-ion battery of the present invention, its preparation method adopts common material preparation processes and battery assembly processes, with a simple process, easy operation, low cost, and is suitable for large-scale industrial production; by precisely controlling each preparation process parameter, the stability and consistency of the product quality are ensured. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] The present invention will be further described below with reference to the accompanying drawings.
[0026] Figure 1 It is a charge-discharge cycle performance curve graph of the sodium-ion battery prepared in Example 1 of the present invention. DETAILED DESCRIPTION OF THE EMBODIMENTS
[0027] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings in the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative efforts shall fall within the protection scope of the present invention.
[0028] The experimental methods in the following embodiments are all conventional methods unless otherwise specified, and are carried out according to the techniques or conditions described in the literature in this field or according to the product specifications. The materials, reagents, etc. used in the following embodiments can be obtained from commercial channels unless otherwise specified.
[0029] Example 1
[0030] This example provides a preparation method for a high-stability and long-life sodium-ion battery, as follows.
[0031] Step 1. Prepare the positive electrode sheet
[0032] Mix Ni(NO3)2, Fe(NO3)3, (NH4)2HPO4, Na3C6H5O7, and Zr 4+ in a molar ratio of (Ni + Fe):P:Na:Zr 4+ = 1.05:1:1.03:0.1, dissolve in deionized water, heat in a 70°C water bath, and continuously stir until the solution becomes a transparent sol (takes 3.5 h), then let it stand for 24 hours to form a gel. Subsequently, quickly freeze the gel in liquid nitrogen and then freeze-dry it (-50°C, vacuum degree of 10 Pa, 24 hours), keep it at 300°C for 2 hours, and then calcine it at 780°C for 11 h in an atmosphere of a mixed gas of nitrogen and hydrogen with a volume ratio of 9:1 to obtain a sodium transition metal phosphate composite material; mix the sodium transition metal phosphate composite material, graphene, and polyvinylidene fluoride in a weight ratio of 81:14:5, then add it to NMP solvent, stir evenly to form a positive electrode slurry with a solute mass fraction of 65%, then coat the positive electrode slurry on the positive electrode current collector, with a coating thickness of 150 um, then dry it at 120°C for 12 h, and finally roll press it to obtain a positive electrode plate with a density of 3.2 g / cm 3 ³.
[0033] Step 2: Prepare the negative electrode plate
[0034] Ball-mill hard carbon at 500 rpm with zirconia grinding balls at a ball-to-material ratio of 20:1 for 20 h to obtain a surface-nanostructured hard carbon material with a specific surface area of 210 m² / g and D50 = 85 nm; mix the surface-nanostructured hard carbon material, acetylene black, and styrene-butadiene rubber in a weight ratio of 84:11:5, then add it to pure water, stir evenly to form a negative electrode slurry with a solute mass fraction of 65%, then coat the negative electrode slurry on the negative electrode current collector, with a coating thickness of 120 um, then dry it at 80°C for 8 h, and finally roll press it to obtain a negative electrode plate with a density of 1.8 g / cm 3 ³.
[0035] Step 3: Prepare the electrolyte
[0036] Dissolve sodium bis(fluorosulfonyl)imide derivative in a mixed solvent composed of ethylene carbonate, dimethyl carbonate, and ethyl methyl carbonate in a volume ratio of 1:1:2 to form a mixed solution with a concentration of 1.2 mol / L; then sequentially add vinylene carbonate with a mass fraction of 1% and 2,7-di-tert-butylphenothiazine with a mass fraction of 0.5% to the mixed solution, and fully stir and mix under argon protection to obtain the electrolyte.
[0037] Step 4: Prepare the sodium-ion battery
[0038] The positive electrode sheet, polyolefin separator, and negative electrode sheet are assembled into an electrode core in sequence, placed into an aluminum-plastic film soft-pack battery case, filled with full-case electrolyte, and processed through encapsulation and formation (charged to 3.8 V at a rate of 0.1C, then discharged to 2.0 V, and cycled 3 times), and finally a sodium-ion battery with high stability and long life is obtained.
[0039] Example 2
[0040] This example provides a method for preparing a sodium-ion battery with high stability and long life. Compared with Example 1, the only difference is that:
[0041] (1) When preparing the positive electrode sheet in Step 1, the sodium transition metal phosphate composite material, graphene, and polyvinylidene fluoride are mixed in a weight ratio of 80:13:5;
[0042] (2) When preparing the negative electrode sheet in Step 2, the surface-nanostructured hard carbon material, acetylene black, and styrene-butadiene rubber are mixed in a weight ratio of 83:10:5;
[0043] Other steps and conditions remain the same, and finally a sodium-ion battery with high stability and long life is prepared.
[0044] Example 3
[0045] This example provides a method for preparing a sodium-ion battery with high stability and long life. Compared with Example 1, the only difference is that:
[0046] (1) When preparing the positive electrode sheet in Step 1, the sodium transition metal phosphate composite material, graphene, and polyvinylidene fluoride are mixed in a weight ratio of 85:12:5;
[0047] (2) When preparing the negative electrode sheet in Step 2, the surface-nanostructured hard carbon material, acetylene black, and styrene-butadiene rubber are mixed in a weight ratio of 84:11:5;
[0048] Other steps and conditions remain the same, and finally a sodium-ion battery with high stability and long life is prepared.
[0049] Comparative Example 1
[0050] This comparative example provides a method for preparing a sodium-ion battery. Compared with Example 1, the only difference is that: when preparing the positive electrode sheet in Step 1, the sodium transition metal phosphate composite material is replaced with Na3V2(PO4)3; other steps and conditions remain the same, and finally a sodium-ion battery is prepared.
[0051] Comparative Example 2
[0052] This comparative example provides a method for preparing a sodium-ion battery. Compared with Example 1, the only difference is that when preparing the negative electrode sheet in Step 2, the surface-nanostructured hard carbon material is replaced with hard carbon; other steps and conditions remain the same, and finally a sodium-ion battery is obtained.
[0053] Comparative Example 3
[0054] This comparative example provides a method for preparing a sodium-ion battery. Compared with Example 1, the only differences are that when preparing the positive electrode sheet in Step 1, the sodium transition metal phosphate composite material is replaced with Na3V2(PO4)3; and when preparing the negative electrode sheet in Step 2, the surface-nanostructured hard carbon material is replaced with hard carbon; other steps and conditions remain the same, and finally a sodium-ion battery is obtained.
[0055] Perform performance tests on the sodium-ion batteries prepared in Examples 1-3 and Comparative Examples 1-3, including cycle life, capacity retention rate, and charge-discharge performance. The detection method is as follows:
[0056] Cycle life: Charge to 3.8V at a rate of 0.1C, then discharge to 2.0V, and cycle several times until the capacity retention rate drops to 80%, and record the number of cycles;
[0057] Capacity retention rate: Charge to 3.8V at a rate of 0.1C, then discharge to 2.0V, and after 1000 cycles, measure and record its capacity retention rate; among them, taking Example 1 as the representative of Examples 1-3, the charge-discharge cycle performance curve diagram as Figure 1 shown is obtained;
[0058] Charge-discharge performance: Measure and record the ratio of the discharge capacity of the battery at 20°C and 0.5C to the discharge capacity at 25°C (room temperature) and 0.5C.
[0059] List the test results in Table 1 as follows: Table 1 is as follows:
[0060] Table 1
[0061] Cycle life / times Capacity retention rate / 100% Charge-discharge performance Example 1 1500 85 0.80 Example 2 1465 83 0.78 Example 3 1450 83 0.75 Comparative example 1 996 70 0.65 Comparative example 2 985 66 0.62 Comparative example 3 801 55 0.55
[0062] Analyze the data in Table 1. It can be known that compared with Comparative Examples 1-3, the sodium-ion batteries prepared in Examples 1-3 have significantly stronger cycle life, capacity retention rate, and charge-discharge performance. This shows that the sodium-ion battery of the present invention has more excellent high stability and long life in terms of electrochemical performance.
[0063] The above has described a detailed description of an embodiment of the present invention, but the content described is only a preferred embodiment of the present invention and cannot be considered as limiting the scope of implementation of the present invention. All equivalent changes and improvements made according to the scope of the application of the present invention should still fall within the scope covered by the patent of the present invention.
Claims
1. A sodium ion battery with high stability and long life, comprising a positive electrode sheet, a negative electrode sheet, an electrolyte and a separator, wherein the positive electrode sheet comprises a positive electrode current collector and a positive electrode active material coated on the positive electrode current collector, and the negative electrode sheet comprises a negative electrode current collector and a negative electrode active material coated on the negative electrode current collector; characterized in that: The positive electrode active material is a sodium transition metal phosphate composite material; the negative electrode active material is a surface nano-hard carbon material.
2. The high-stability and long-life sodium-ion battery according to claim 1, wherein The preparation method of the sodium transition metal phosphate composite material is as follows: a transition metal salt, a phosphate source, a sodium source, and a dopant are mixed in a molar ratio of metal ion: P: Na: doping ion = 1.05:1:1.03:0.1, a precursor is prepared by a sol-gel method, and then calcined at 750-800° C. for 10-12 hours in a mixed gas atmosphere of nitrogen and hydrogen to obtain the sodium transition metal phosphate composite material.
3. The high-stability and long-life sodium-ion battery according to claim 2, wherein The preparation method of the precursor using the sol-gel method is as follows: Dissolve the transition metal salt in deionized water, mix the transition metal salt, phosphate source, sodium source and dopant in proportion and then dissolve in deionized water, heat in a water bath at 60-80°C, and continue stirring until the solution becomes a transparent sol, then let it stand for 24 hours to form a gel, then quickly freeze the gel with liquid nitrogen and freeze-dry it, and keep it warm at 300°C for 2 hours.
4. The sodium ion battery with high stability and long life according to claim 2, characterized in that: The transition metal salt is manganese sulfate, cobalt nitrate, nickel nitrate, iron nitrate, manganese acetate, cobalt oxalate, iron chloride, and / or; the phosphorus source is ammonium dihydrogen phosphate, diammonium hydrogen phosphate, sodium phosphate, sodium pyrophosphate, phosphoric acid, and / or; the sodium source is sodium bicarbonate, sodium acetate, sodium oxalate, sodium citrate, sodium nitrate, and / or; the dopant is Mg 2+ , Al 3+ , Ti 4+ , Zr 4+ , F - , and / or.
5. The high-stability and long-life sodium-ion battery according to claim 2, characterized in that, The preparation method of the positive electrode sheet is as follows: Mix a sodium transition metal phosphate composite material, a conductive agent, and a binder in a weight ratio of (80-82):(15-13):5, then add them to an N-methylpyrrolidone solvent, stir evenly to form a positive electrode slurry, and then coat the positive electrode slurry on a positive electrode current collector with a coating thickness of 145-155 μm. After drying, roll press to obtain a positive electrode sheet with a density of 3.2 g / cm 3 ³.
6. The high-stability and long-life sodium-ion battery according to claim 1, wherein The preparation method of the surface nano-hard carbon material is as follows: hard carbon is ball-milled for 20 hours at 500 rpm using zirconium oxide grinding balls at a ball-to-material ratio of 20:1 to obtain the surface nano-hard carbon material.
7. The high-stability and long-life sodium-ion battery according to claim 6, characterized in that, The preparation method of the negative electrode plate is as follows: Mix the surface-nanostructured hard carbon material, conductive agent, and binder in a weight ratio of (83-85):(10-12):5, then add pure water, stir evenly to form a negative electrode slurry, and then coat the negative electrode slurry on the negative electrode current collector, with a coating thickness of 115-125 μm. After drying, roll press to obtain a negative electrode plate with a density of 1.8 g / cm 3 ³.
8. The high-stability and long-life sodium-ion battery according to claim 1, wherein The preparation method of the electrolyte is: dissolving a conductive sodium salt in an organic solvent to form a mixed solution with a concentration of 1.2 mol / L; then adding a functional additive to the mixed solution, and fully stirring and mixing under argon protection to obtain the electrolyte.
9. The high-stability and long-life sodium-ion battery according to claim 8, wherein; The conductive sodium salt is a sodium bis(fluorosulfonyl)imide derivative; the organic solvent is a mixed solvent composed of ethylene carbonate, dimethyl carbonate and ethyl methyl carbonate in a volume ratio of 1:1:2; the functional additives include film-forming additives and antioxidant additives, wherein the film-forming additive is vinylene carbonate and the antioxidant additive is 2,7-di-tert-butylphenothiazine.
10. A method for preparing a sodium ion battery with high stability and long life according to any one of claims 1-9, characterized in that, The method comprises the following steps: assembling a positive electrode sheet, a separator and a negative electrode sheet into a battery cell in sequence, placing the battery cell into a battery shell, injecting an electrolyte, and finally obtaining the sodium ion battery with high stability and long life through packaging and chemical formation processes.